Audit committee busyness and financial reporting quality - Mohamad Azlan, Jaafar (2016)
The objective of this study is to investigate the busyness of audit committee and its relationship with financial reporting quality. Increasing corporate governance reforms have made the responsibilities of audit committee more onerous; therefore, there is now widespread concern whether busy audit committees can carry out their monitoring duties effectively. To address the concern with audit committee busyness in an emerging economy like Malaysia, the study, which is drawn from the agency and resource dependence theories, examines if there is any relationship between audit committee busyness and financial reporting quality. The samples in this study comprise the top 150 listed companies in Malaysia, where audit committee busyness is analysed from the perspective of multiple directorships and overlapping board committees, using audit delay and financial restatements as proxies to financial reporting quality. It is observed that financial experts on the audit committee are busier than non-financial experts in terms of multiple directorships. Similarly, the audit committee chair has significantly higher multiple directorships than non-chair members. Findings from the study reveal that the presence of an audit committee financial expert in the remuneration committee is an important determinant to reduce audit delay. The relationship between multiple directorships of audit committee and audit report delay is also found to be statistically significant. Further evidence suggests that companies whose audit committee chair has overlapping membership, are more likely to restate their financial statement. Findings from this study also indicate that the overlapping committee membership of audit committee financial experts is significantly and negatively related to financial restatement. Findings from this study provide additional knowledge by suggesting that the board needs to examine the busyness of the audit committee chair and financial experts separately to improve the company's financial reporting quality. This would be relevant to policy-makers in evaluating the merits of regulating multiple directorships.